Impacts of a multipronged initiative with community HIV clinics to support retention and re-engagement in HIV care - Ellen Eaton; Claudia T. Martorell; Jewel Sawyer; Tanya S. Schreibman; Gregory S. Felzien; Jenniffer Meza Jimenez; Chelsie Anderson Chadha; Jeffrey Carter; Chris Napolitan; Laura Simone; Leah Molloy; Bonnie Douglas (HIV Research & Clinical Practice)
Background Despite advances in HIV treatment, gaps in care retention threaten the individual health of people with HIV (people) and public health efforts to end the HIV epidemic. Objective This project aimed to identify and address gaps in retention and support re-engagement in care. Methods A multipronged initiative at five community HIV clinics and community-based organizations (CBOs) included patient, healthcare professional (HCP), and community-focused interventions. Patient-oriented interventions included instructional videos for patients to view before appointments and conversation guides about barriers to care for patients to use with staff during appointments. HCP-oriented interventions included baseline surveys assessing clinic practices and challenges and audit-feedback sessions to review survey findings and devise plans to improve retention strategies. Community-oriented interventions included education sessions co-led by clinics and CBOs, micro-learning engagements at community events, and social media campaigns covering topics related to HIV care. Data were collected through surveys administered before and after patient- and HCP-oriented interventions and community education sessions, follow-up surveys administered after micro-learning engagements, and reach of social media campaigns. Results Patient-oriented interventions led to improvements in patient-reported empowerment and confidence in their ability to remain in care. HCPs also reported improvements in patient intake and follow-up processes after audit-feedback sessions. Community interventions reached over 1,000 community members combined, with education sessions and micro-learning engagements uncovering key barriers to HIV care and leading to improvements in knowledge and awareness of local HIV services. Conclusion This multipronged initiative demonstrates how patient, HCP, and community-oriented education can support retention and re-engagement in care.